The effect of cyanoacrylate infiltration on microstructure of hydroxyapatite/chitosan composite - Purnomo -; Endang Tri Wahyuni Maharani (Universitas Muhammadiyah Semarang, 2016)
Abstract. Brittle nature of hydroxyapatite for bone implants reduced by adding chitosan. To strengthen the particles bond of the composite, cyanoacrylate was infiltrated into the composites. Infiltration was performed at room temperature and without any external pressure treatment system. The aim of this study is to examine the microstructure of hydroxyapatite-chitosan composite by infiltration of cyanoacrylate. Hydroxyapatite composite-chitosan composit was immersed in cyanoacrylate. Cyanoacrylate infiltrate into composite from all directions. The system is isolated from atmospheric air in order to avoid direct contact with air. Surface morphology was observed by scanning electron microscope on the specimen. Observations indicate that the higher content of chitosan, cyanoacrylate increasingly looks much infiltrated composite hydroxyapatite-chitosan.